2021
DOI: 10.3390/encyclopedia1010012
|View full text |Cite
|
Sign up to set email alerts
|

Generational Effects of Opioid Exposure

Abstract: The inheritance of substance abuse, including opioid abuse, may be influenced by genetic and non-genetic factors related to the environment, such as stress and socioeconomic status. These non-genetic influences on the heritability of a trait can be attributed to epigenetics. Epigenetic inheritance can result from modifications passed down from the mother, father, or both, resulting in either maternal, paternal, or parental epigenetic inheritance, respectively. These epigenetic modifications can be passed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…A second question is whether the effects we observe exact a toll on health and cognition throughout childhood and adulthood. Future work should explore whether the timing and intensity of opioids in utero bear any long-term, causal consequences on children’s physical or mental health, cognitive ability, or behaviors as evidenced by several observational studies (Nygaard et al 2020; Odegaard, Pendyala, and Yelamanchili 2021). If, on one hand, the estimated effects of in utero exposure are indeed inflated at birth and fade later in life, we might conclude that when chronic opioid use is indicated, the benefits to the mother might outweigh the short-lived risks to infants, such as NAS and encounters with the child welfare system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second question is whether the effects we observe exact a toll on health and cognition throughout childhood and adulthood. Future work should explore whether the timing and intensity of opioids in utero bear any long-term, causal consequences on children’s physical or mental health, cognitive ability, or behaviors as evidenced by several observational studies (Nygaard et al 2020; Odegaard, Pendyala, and Yelamanchili 2021). If, on one hand, the estimated effects of in utero exposure are indeed inflated at birth and fade later in life, we might conclude that when chronic opioid use is indicated, the benefits to the mother might outweigh the short-lived risks to infants, such as NAS and encounters with the child welfare system.…”
Section: Discussionmentioning
confidence: 99%
“…Although these estimated effects are consistent, the causal effect of in utero opioid exposure on short- and long-term health and well-being remains unknown. Given the mounting empirical evidence demonstrating that adulthood health and well-being are determined in part by the fetal environment and health at birth (Almond and Currie 2011; Almond, Currie, and Duque 2018), researchers anticipate that any short-term causal effects might translate into disparities in health and human capital later in life (Nygaard et al 2015; Odegaard, Pendyala, and Yelamanchili 2021).…”
mentioning
confidence: 99%
“…8 However, only less than 10 species of Bifidobacterium are commercialized as probiotic strains nowadays, although this genus comprises 82 species and 12 subspecies. 9 Thus, it is important to identify and develop a novel Bifidobacterium strain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For this reason, there has been a development of dairy products and dietary supplements containing Bifidobacterium for adult consumption . However, only less than 10 species of Bifidobacterium are commercialized as probiotic strains nowadays, although this genus comprises 82 species and 12 subspecies . Thus, it is important to identify and develop a novel Bifidobacterium strain.…”
Section: Introductionmentioning
confidence: 99%
“…Despite having approximately one-tenth the potency of morphine [2], oxy has demonstrated a comparable ability to cross the blood-brain barrier (BBB) and inflict neuronal damage [3]. Further, previous studies have identified that offspring born to opioid-exposed mothers exhibit a number of deficits in development and behavior, as well as molecular alterations, impacting synaptic signaling [4]. Oxy exposure, specifically, has been shown to impact the expression of miRNA cargoes within extracellular vesicles, creating a potential for impaired patterns of neurodevelopment [5].…”
Section: Introductionmentioning
confidence: 99%